Evaluation of the current status and risks of aquatic ecology in the Jialing River Basin based on the characteristics and succession trends of phytoplankton communities - Maojin Huang; Fei Xu; Jia Xia; Xue Yang; Fubin Zhang; Siyao Liu; Tuo Zhang (Ecological Indicators)
River ecosystems are vital for maintaining ecosystem balance but rapid development in China’s Yangtze River Basin has led to severe ecological degradation. Therefore, this study aimed to evaluate the aquatic ecosystem health of the Jialing River Basin, investigate the influencing factors of the aquatic ecology, and predict the succession trend of the phytoplankton community. Phytoplankton was collected in the Jialing River (Nanchong section) and one of its tributaries (Xichong River). Morphological identification methods, random forest, neutral community model, and modified stochasticity ratio were used to analyze phytoplankton composition, environmental drivers, and community assembly mechanisms. The results showed that 1) Bacillariophyta, Cryptophyta, and Chlorophyta were the dominant phyla in the Jialing River, followed by Cyanobacteria. The structure of the phytoplankton community was affected by seasonal changes and differences in the tributary and mainstem. 2) Overall, the autumn phytoplankton community α-diversity index was significantly higher than that of spring (P < 0.05). The aquatic ecosystem health was better in autumn than in spring and in the mainstem than in the tributary. 3) Ammonia nitrogen and permanganate indices were key drivers of community composition in the tributary, while the main stem was negatively correlated with total phosphorus, ammonia nitrogen, and permanganate indices. 4) Stochastic processes dominated the assembly of phytoplankton communities in spring in the Jialing River, while autumn in the Jialing and Xichong Rivers (tributary river) and spring in the Xichong River were mainly dominated by deterministic processes. In summary, the spatial and temporal variations of phytoplankton communities in the Jialing River lead to different aquatic ecosystem health states, which are essentially driven by the aggregation mechanism of phytoplankton communities. These results provide a theoretical basis for predicting the aquatic environment of the Jialing River and inform the environmental management of the basin.